Emotional Consequences in Harassed Women from a Public (Government) Institution - Reyes, Maria Kenya Lopez; Espinosa, Ana Maria Alejandra Herrera; Romero, Raul Rocha (European Scientific Journal, ESJ, 2017)
The aim of this study is to identify the emotional consequences in workers occupationally harassed in a public institution in the state of Puebla, Mexico. We conducted semi-structured interviews to 6 employees. There were obtained 9 categories of Harassment in the Workplace: feelings of harassment, types of violence at work, personal beliefs, personality traits of the harasser, emotions, emotional consequences, to the institution, perspective to the harassment and perspective to the emotional regulation. The results of the contents analysis show the emotional regulation is difficult to manage in people who suffer harassment at work, that there is emotional repression in the face of the events of harassment in the workplace to express feelings toward his stalker and that vulnerability is not an emotion expressed in the workers who suffer harassment in the workplace. Emotions such as anger, fear, helplessness and frustration are some of the emotional consequences in victims, as well as the predisposition to harassment and distrust of authority figures, influencing in a negative way to these female employees in a cognitive level, emotional, social and to work policies.